HUBUNGAN TINGKAT PENDIDIKAN DAN PENGETAHUAN ORANG TUA TENTANG KEBERSIHAN GIGI DAN MULUT PADA ANAK BALITA 3 – 5 TAHUN DENGAN TINGKAT KEJADIAN KARIES GIGI DI RA PERWANIDA PLIKEN KEMBARAN BANYUMAS - Wahyudi, Wahyudi; Kuswati, Ani (JURNAL KEPERAWATAN MERSI, 2013)
Child of age 2-4 years has exasperation to eat sweet food, while old fellow unable to mind habit to tie tooth, if a chlid do not want to brush teeth hence as a stripper better can force its(the chlid to brush teeth especially when nearing night sleep. If(when an unaccustomed chlid brushs teeth hence from the habit can cause chlid experiencing caries. Observation result done by 50 pupils RA Perwanida Pliken Kembaran Banyumas is got by pupil data having caries tooth counted 86% while pupil that is is not has caries tooth counted 14%. Out of 30 pupils having caries tooth to tell that they seldom brush teeth, and level of education of old fellow is varying Purpose of research is know are there relation between level of education, knowledge and position of old fellow about hygiene of tooth and oral with caries case. And know caries causes at balita in RA Perwanida Pliken Kembaran Banyumas. This research is quantitative research with planning cross sectional. Population in this research is all old fellows or pupil sponsor in RA Perwanida Pliken Kembaran Banyumas which amounts to 35 with number of samples 30. Data processing technique applies analytical technique Chi Square. The research conclusion indicates that ( 1) Level of education of student old fellow RA Perwanida Pliken Kembaran Banyumas average of SD and SMP, (2) Knowledge of student old fellow RA Perwanida Pliken Kembaran Banyumas medium mean, (3) There are no relationship signifikan level of education of old fellow with case of caries at child of balita in RA Perwanida Pliken Kembaran Banyumas, and (4) There is relationship signifikan knowledge of old fellow with case of caries at child of balita in RA Perwanida Pliken Kembaran Banyumas.